The Influence Of Personal Protective Equipment (PPE)Based On The Biological And Psychological Aspects Of Nurses In The Covid-19 Pandemic - Tria anisa; Ni Kadek diah; Shinta Bella; Ana Pinata; Melania Belqis; Alfi Dwi Agustina (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2023)
Introduction : The Covid-19 pandemic is a big challenge in the world of health, including nursing. Nurses are the main stronghold in patient care because nurses meet patients more frequently and longer than other medical personnel. The use of PPE is urgently needed in treating patients with Covid-19, the impact of using PPE cannot be avoided and can affect nurses, feelings of discomfort and poor physical condition can result in a decrease in both physical and psychological health. Purpose: This article review aims to determine the impact of using PPE on nurses' physical and psychological health during a pandemic. Method: This article was reviewed by identifying articles in the last 5 years with the theme of the effect of the use of PPE on the physiology and psychology of nurses during a pandemic with the original article inclusion criteria. Results: This article review collects articles from Google Scholar and ScienceDirect keywords used PPE, covid19, nurse, physical aspect, and biological aspect. The results of the identification resulted in 15 articles that met the inclusion and exclusion criteria. Conclusion: PPE has an impact on the physical aspects, namely respiratory disorders and fatigue. Influences on the psychological aspects are stress, depression, and anxiety. Nurses must have physical and mental health preparations to face various challenges in patient care processes and procedures during the Covid-19 pandemic.